2013
DOI: 10.1190/geo2012-0090.1
|View full text |Cite
|
Sign up to set email alerts
|

A new optimization approach for source-encoding full-waveform inversion

Abstract: Waveform inversion is the method of choice for determining a highly heterogeneous subsurface structure. However, conventional waveform inversion requires that the wavefield for each source is computed separately. This makes it very expensive for realistic 3D seismic surveys. Source-encoding waveform inversion, in which the sources are modeled simultaneously, is considerably faster than conventional waveform inversion but suffers from artifacts. These artifacts can partly be removed by assigning random weights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…In order to alleviate the large computational burden presented by sequential waveform inversion methods (e.g., Algorithm 1), a source encoding method has been proposed [22], [29], [41]. This method has been formulated as a stochastic optimization problem and solved by various stochastic gradient-based algorithms [30], [31]. In this section, we adapt the stochastic optimization-based formulation in [30] to find the solution of Eqn.…”
Section: B Stochastic Optimization-based Waveform Inversion With Soumentioning
confidence: 99%
See 1 more Smart Citation
“…In order to alleviate the large computational burden presented by sequential waveform inversion methods (e.g., Algorithm 1), a source encoding method has been proposed [22], [29], [41]. This method has been formulated as a stochastic optimization problem and solved by various stochastic gradient-based algorithms [30], [31]. In this section, we adapt the stochastic optimization-based formulation in [30] to find the solution of Eqn.…”
Section: B Stochastic Optimization-based Waveform Inversion With Soumentioning
confidence: 99%
“…However, to accomplish this, the data fidelity term in Eqn. (9) is reformulated as the expectation of a random quantity as [29]- [31], [33], [41], [42]…”
Section: B Stochastic Optimization-based Waveform Inversion With Soumentioning
confidence: 99%
“…This common limitation of non-convex problems can be partially mitigated by choosing the compression thresholds adaptively based on the norm of the gradient, thus gradually including more information. Similar strategies in the context of stochastic gradient methods have been applied successfully in full-waveform inversion (Li et al, 2012;Moghaddam et al, 2013), where randomly chosen subsets of sources introduce inexactness in the gradient. It has been observed by van Herrmann (2013, 2014) that the level of inexactness can be quite high during the first iterations and only needs to be refined once a local minimum is approached.…”
Section: Discussionmentioning
confidence: 99%
“…The computational cost is directly proportional to the sample size b = |I|, and thus a higher error in the gradient directly translates into a lower computational cost. Numerical experiments have shown that this approach is beneficial on 2D seismic inversion problems [49,28]. How to choose the rate of increase of the sample size in practice is an open problem.…”
Section: Source Subsamplingmentioning
confidence: 99%